Role of the Peroxisome Proliferator-Activated Receptors, Adenosine Monophosphate-Activated Kinase, and Adiponectin in the Ovary - Joëlle Dupont; Christine Chabrolle; Christelle Ramé; Lucie Tosca; Stéphanie Coyral-Castel (PPAR Research)
The mechanisms controlling the interaction between energy balance and reproduction are the subject of intensive investigations. The integrated control of these systems is probably a multifaceted phenomenon involving an array of signals governing energy homeostasis, metabolism, and fertility. Two fuel sensors, PPARs, a superfamily of nuclear receptors and the kinase AMPK, integrate energy control and lipid and glucose homeostasis. Adiponectin, one of the adipocyte-derived factors mediate its actions through the AMPK or PPARs pathway. These three molecules are expressed in the ovary, raising questions about the biological actions of fuel sensors in fertility and the use of these molecules to treat fertility problems. This review will highlight the expression and putative role of PPARs, AMPK, and adiponectin in the ovary, particularly during folliculogenesis, steroidogenesis, and oocyte maturation.